(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
The concept of patient safety has been developed due to the increased incidence of medical error in Indonesia. Although incidents related to patient safety occurs in health servicessuch as the Independent Practice of Midwifery or BidanPraktikMandiri(BPM), it has not received enough attention from the stakeholders. This research discusses the implementationof Patient Safety Model atthe Independent Practice of Midwiferyin Bogor District, West Java Province. The research was conducted with mixed method approach, using threeway phase. The first phase is the construction on patient safety goals in BPM by doing focus group discussion on 3 groups and 2 in-depth interviews with 2 informants. The second phase is the model development in the form of validation based on findings in the first phase. Additionally, phase 2 is done by using crosssectional design of 90 midwives and SEM analysis using PLS. The third phase is conducting a quantitative evaluation model with pre and post design at 30 BPM which have had training on Patient Safety Model. The findings show allvariables (patient safety goals, knowledge, attitudes, motivations, and behaviors related to the patient safety) are valid in shaping Patient Safety Model. The results on Model application evaluation (phase 3) indicate that the model effective in increasing knowledge (p 0.000), attitude (p 0.000), motivation (p 0.000) and behavior (p 0.001) on patient safety in BPM.